Characterisation of bacterial nanocellulose and nanostructured carbon produced from crude glycerol by Komagataeibacter sucrofermentans. (December 2021) - Lee, Saehee; Abraham, Amith; Lim, Alan Christian S.; Choi, Okkyoung; Seo, Jeong Gil; Sang, Byoung-In
Graphical abstract: Highlights: Biodiesel-derived crude glycerol was used for BNC production by K. sucrofermentans . High crystallinity (85%) and tensile strength of the BNC films were obtained. Excellent capacitance of the carbon material derived from the BNC was observed. Abstract: Bacterial nanocellulose (BNC), which has tunable properties, is a precursor of nanostructured energy storage materials; however, the cost of BNC production is challenging. This study uses crude glycerol from the biodiesel industry as a carbon nutrient and first-time carbonised BNC from K. sucrofermentans that is applied in energy storage. From crude glycerol in static cultivation, 6.4 g L -1 BNC was produced with a high crystallinity index (85%) and tensile properties in comparison to conventionally used pure carbon substrates. Carbon materials were derived from the BNC retained fibrous and crystalline features with disordered porous structures. The electrochemical properties of the carbon materials have a specific capacitance of 140 F g −1 . This study highlights the valorisation of waste glycerol from the biodiesel industry as a substrate for efficient BNC production and the energy storage potential of carbon derived from BNC as renewable energy materials.